Capacidad germinativa de semillas de 32 especies de malezas - Doll, Jerry D.; Piedrahíta Castañeda, Wilson; Argel M., Pedro J. (1976)
Information is lacking concerning the viability and longevity of weed seeds in tropical Latin America. This study observed the germinative ability of seeds of 20 weed species common in annual crops and 12 common pasture weeds for two years. They were collected, cleaned and stored dry in the laboratory. Every two months, germination tests were run with 300 seeds of each species. Much variation was found in the germination patterns. In general, the grassy weeds lost their viability sooner than the dicotyledonous species. Rottboellia exaltata was the grassy weed with the greatest germinative ability during the two years, while Portulaca oleacea and Ipomoea hederifolia had the highest among the broadleaf weeds. The pasture weed species had generally lower germination percentages than did the crop weed species. Five of the former completely lost their viability in the course of the study. If the same occurs under natural field conditions, it would perhaps be possible with a vigorous control and vigilence program to erradicate these species in two years or less, and prevent new seeds from being reproduced.